Program Pendampingan Disain Kawasan RTH dan Resapan Air di TPU Muslim Al-lkhlas Kelurahan Sungai Bangkong Kota Pontianak - Zairin Zain; Irwin Irwin; Uray Fery Andi; Jawas Dwijo Putro (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2020)
TPU Muslim Al-lkhlas in the district of Sungai Bangkong is one of the largest burial ground in Pontianak City, with an area of ​​approximately 4 hectares. The TPU Muslim Al-lkhlas is in the city center, and it requires better management to be able to serve as a Green Open Space (RTH) and a water absorption area in Pontianak City. Regulation of Ministry of Public Works No. 5/2008 concerning Guidelines for Provision and Utilization of Green Open Space in Urban Areas is a reference in the design assistance program for TPU Muslim Al-Ikhlas in the district of Sungai Bangkong as RTH and Water Absorption Areas. The new design of the TPU Muslim Al-Ikhlas is intended to restore the ecological function of the tomb as a water absorption area, a place for the growth of various types of vegetation, generator of microclimate, a place to live birds with social functions of the surrounding community. Careful planning is part of the realization of caring to build a neat and beautiful burial ground with a service of Green Open Space for social and recreational activities and also serves as water absorption areas.